"Click-chemical" modification of cellulose acetate nanofibers: a versatile platform for biofunctionalization. Issue 28 (2nd July 2018) - Dong, Yishi; Lu, Xiaowen; Wang, Peixi; Liu, Wenying; Zhang, Shuxiang; Wu, Zhaoqiang; Chen, Hong
Abstract : We demonstrated a platform for the biofunctionalization of cellulose acetate nanofibers using a new type of click chemistry, namely "sulfur(vi )–fluoride exchange reaction". Abstract : Cellulose acetate nanofibers have attracted considerable interest in the biomedical sciences, but lack convenient biofunctionalization methods. In this work the "sulfur(vi )–fluoride exchange reaction", a new type of click chemistry, is used for the first time to overcome many of the difficulties previously encountered and provide a platform for biofunctionalization generally.